Is there any association between the presence of biomarkers and apical periodontitis? A systematic review - Matos-Sousa, José Mário; Chemelo, Victória Santos; Frazão, Deborah Ribeiro; Bittencourt, Leonardo Oliveira; Moura, João Daniel Mendonça de; Mesquita, Caio Melo; Marañón-Vásquez, Guido; Fagundes, Nathalia Carolina Fernandes; Paranhos, Luiz Renato; Maia, Lucianne Cople; Monteiro, Marta Chagas; Lima, Rafael Rodrigues (Frontiers in Immunology, 2024)
This systematic review aimed to verify whether there is evidence of an association between apical periodontitis and the presence of systemic biomarkers. This study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses - PRISMA. For this, the acronym PECO was used; population (P) of adult humans exposed (E) to the presence of apical periodontitis, compared (C) to adult humans without apical periodontitis, and the outcome (O) of the presence of biomarkers was observed. The articles were searched in PubMed, Scopus, Web of Science, LILACS, Cochrane Library, OpenGray, and Google Scholar grey databases. Subsequently, studies were excluded based on title, abstract, and full article reading, following the eligibility criteria. The methodological quality of the selected studies was evaluated using the Newcastle-Ottawa qualifier. After exclusion, 656 studies were identified, resulting in 17 final articles that were divided into case-control, cross-sectional, and cohort studies. Eight studies were considered to have a low risk of bias, one had a medium risk of bias, and eight had a high risk of bias. In addition, 12 articles evaluated biomarkers in blood plasma, four evaluated them in saliva, and only one evaluated them in gingival crevicular fluid. The results of these studies indicated an association between apical periodontitis and the systemic presence of biomarkers. These markers are mainly related to inflammation, such as interleukins IL-1, IL-2, and IL-6, oxidative markers, such as nitric oxide and superoxide anions, and immunoglobulins IgG and IgM.